Density Tunable Graphene Aerogels Using a Sacrificial Polycyclic Aromatic Hydrocarbon. Issue 11 (9th August 2017) - Turner, Sally; Long, Hu; Shevitski, Brian; Pham, Thang; Lorenzo, Maydelle; Kennedy, Ellis; Aloni, Shaul; Worsley, Marcus; Zettl, Alex
Abstract : We demonstrate a new strategy to tune the density of graphene aerogels. This facile method is capable of producing graphene aerogels over a wide density range without compromising the morphology or quality of the material. Perylenetetracarboxylic acid dianydride serves as a sacrificial filler material that can be thermally decomposed to yield a graphene aerogel with tunable density. Abstract : Graphene aerogels with a wide range of densities are prepared using a polycyclic aromatic hydrocarbon as a sacrifical molecule. Using this method, densities as low as half that of a control graphene aerogel and three times more dense than the control can be realized and are shown in the figure.